Artificial Intelligence In Homoeopathy: Supportive Tool Or Silent Threat? - Shinde, Shubham; Nair, Parvathi (Homoeopathic Heritage, 2026)
Artificial intelligence (AI) has rapidly expanded its role in healthcare, with growing interest in its application within the homoeopathic system of medicine. Homoeopathy is a holistic system that relies on detailed case taking, individualisation, and the physician's clinical judgment. Recent advancements such as computerized repertorisation, digital materia medica, electronic case records, and data-driven analysis have introduced AI as a supportive tool in the homoeopathic practice. These technologies can improve efficiency, assist in complex case analysis, enhance research, and support education and patient management. However, the increasing use of artificial intelligence also raises important concerns. Overdependence on AI may encourage mechanical prescribing, compromise the principle of individualisation, and reduce the essential human elements of empathy and unprejudiced observation. Ethical issues related to data privacy, confidentiality, and clinical accountability further challenge its unrestricted use. This article examines the applications, benefits, and limitations of artificial intelligence in Homoeopathy and emphasizes the importance of a balanced and ethical integration, where AI supports clinical practice while the homoeopathic physician retains authority over diagnosis, remedy selection, and patient care.